An insight on the legal treatment of sexist advertising in Peru - Vidal Cabeza de Tarazona, Gisela Hortencia (2013)
Based on the analysis of three decisions issued by the Commission of Repression of UnfairCompetition of the National Institute for the Defense of Competition and Intellectual Property(INDECOPI), this article provides an insight on the legal treatment applicable to the challengedadvertising as an infringement of the rights of dignity and non-discrimination against women (sexistadvertising) making a comparison with the current legal system.